Penelitian Kualitatif. Komunikasi, Ekonomi, Kebijakan Publik, dan Ilmu Sosial lainnya - BUNGIN, Burhan (Kencana, 2009)
Penelitian Kualitatif. Komunikasi, Ekonomi, Kebijakan Publik, dan Ilmu Sosial lainnya